Dynamic 2D and 3D mapping of hyperpolarized pyruvate to lactate conversion in vivo with efficient multi‐echo balanced steady‐state free precession at 3 T. (10th March 2020) - Müller, Christoph A.; Hundshammer, Christian; Braeuer, Miriam; Skinner, Jason G.; Berner, Stephan; Leupold, Jochen; Düwel, Stephan; Nekolla, Stephan G.; Månsson, Sven; Hansen, Adam E.; von Elverfeldt, Dominik; Ardenkjaer‐Larsen, Jan H.; et al.
Abstract: The aim of this study was to acquire the transient MRI signal of hyperpolarized tracers and their metabolites efficiently, for which specialized imaging sequences are required. In this work, a multi‐echo balanced steady‐state free precession (me‐bSSFP) sequence with Iterative Decomposition with Echo Asymmetry and Least squares estimation (IDEAL) reconstruction was implemented on a clinical 3 T positron‐emission tomography/MRI system for fast 2D and 3D metabolic imaging. Simulations were conducted to obtain signal‐efficient sequence protocols for the metabolic imaging of hyperpolarized biomolecules. The sequence was applied in vitro and in vivo for probing the enzymatic exchange of hyperpolarized [1– 13 C]pyruvate and [1– 13 C]lactate. Chemical shift resolution was achieved using a least‐square, iterative chemical species separation algorithm in the reconstruction. In vitro, metabolic conversion rate measurements from me‐bSSFP were compared with NMR spectroscopy and free induction decay‐chemical shift imaging (FID‐CSI). In vivo, a rat MAT‐B‐III tumor model was imaged with me‐bSSFP and FID‐CSI. 2D metabolite maps of [1– 13 C]pyruvate and [1– 13 C]lactate acquired with me‐bSSFP showed the same spatial distributions as FID‐CSI. The pyruvate‐lactate conversion kinetics measured with me‐bSSFP and NMR corresponded well. Dynamic 2D metabolite mapping with me‐bSSFP enabled the acquisition of up to 420 time frames (scan time: 180‐350 ms/frame) before the hyperpolarized [1– 13 C]pyruvate was relaxed below noise level. 3D metabolite mapping with a large field of view (180 × 180 × 48 mm 3 ) and high spatial resolution (5.6 × 5.6 × 2 mm 3 ) was conducted with me‐bSSFP in a scan time of 8.2 seconds. It was concluded that Me‐bSSFP improves the spatial and temporal resolution for metabolic imaging of hyperpolarized [1– 13 C]pyruvate and [1– 13 C]lactate compared with either of the FID‐CSI or EPSI methods reported at 3 T, providing new possibilities for clinical and preclinical applications. Abstract : 2D and 3D dynamic hyperpolarized 13 C MR spectroscopic imaging were conducted at 3 T using a multi‐echo balanced steady‐state free precession sequence and Iterative Decomposition with Echo Asymmetry and Least squares estimation reconstruction. The sequence was specialized to image pyruvate to lactate conversion with high temporal and spatial resolution in vitro and in vivo. High SNR, improved resolution in shorter scan time and more efficient usage of the magnetization was found compared with a free induction decay‐chemical shift imaging sequence.